An acute case of herpes zoster ophthalmicus with post-herpetic neuralgia and cranial nerve neuropathies - Dadu, Fahad; Kumar, Sathish; R., Sadhana; M., Ramkumar; Kumar, Magesh (International Journal of Advances in Medicine, 2022)
Herpes zoster is a common diagnosis in the emergency department which is caused by reactivation of varicella zoster virus (VZV). Reactivation in ophthalmic division of trigeminal nerve causes Herpes zoster ophthalmicus. It is associated with a rash in the distribution of the trigeminal nerve dermatomes especially in ophthalmic and maxillary divisions. The most often complications of HZO are episcleritis, keratitis, glaucoma, and cataracts. HZO with cranial neuropathy is a very rare condition. So herewith we report a case 51 years old female with swelling, redness in right eye and drooping of eyelids on the right side. She had tearing and double vision. She was diagnosed with herpes zoster ophthalmicus with neuropathy of 3rd, 4th and 6th cranial nerves. The patient was treated and discharged in a healthy condition. Timely diagnosis and treatment can decrease morbidity and prevent the complication.